Low-carbon permeable paving material and preparation method thereof

By using corrugated pavement structure design and composite mineral powder, the problems of insufficient permeability and strength of permeable pavement materials have been solved, realizing permeable pavement materials that are highly permeable, have improved strength, and are low-carbon and environmentally friendly.

CN121473192APending Publication Date: 2026-02-06NANJING DONGRUI TENACITY RES INST CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511732138.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-24
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing permeable pavement materials are insufficient in terms of permeability and overall strength, and cannot effectively improve the problems of urban heat island effect and groundwater shortage.

Method used

The corrugated pavement structure design utilizes the corrugated structure of the permeable concrete base layer and surface layer, combined with composite mineral powder and polymer emulsion, to form a UV-shaped permeable concrete base layer and surface layer, optimizing the permeability path and mechanical properties.

Benefits of technology

It improves the permeability and overall strength of permeable pavements, enhances their load-bearing capacity, compressive strength and seismic resistance, optimizes material utilization, reduces material consumption, and improves environmental adaptability and construction cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121473192A_ABST
    Figure CN121473192A_ABST
Patent Text Reader

Abstract

The invention discloses a low-carbon permeable paving material and a preparation method thereof, the upper surface of a permeable concrete base layer and the lower surface of a permeable concrete surface layer of the paving material are corrugated, and the corrugated peaks and the corrugated valleys of the permeable concrete base layer and the permeable concrete surface layer are mutually inlaid and paved. Crushing fly ash, adding the regenerated powder, vermiculite, diatomite, bentonite and zeolite, and carrying out ball milling to obtain composite mineral powder; crushing an original pavement building material to obtain recycled aggregate; stirring the 7-10mm recycled aggregate with deionized water, mineral powder and polymer emulsion to obtain a permeable concrete base layer paving material; 3-7 mm recycled aggregate, deionized water, composite mineral powder and polymer emulsion are stirred to obtain a permeable concrete surface layer paving material, and a base layer is paved on a sand and gravel grading layer and is compacted and cured by a corrugated road roller to form a permeable concrete base layer of a corrugated structure; and paving the surface layer on the base layer, and compacting and curing by a road roller to form the low-carbon permeable pavement. The water permeable path is changed, the water permeable area and the water permeable mode are increased, blockage is prevented, and the water permeable efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of building materials, in particular to a low-carbon type water-permeable paving material and a preparation method thereof. BACKGROUND

[0002] With the rapid development of China's economy and the acceleration of urban construction, the ground of the city has been gradually covered by buildings and concrete pavements, and the area of water-permeable vegetation is becoming less and less. The non-permeable ground surface brings many negative effects to the ecological cycle of the city. Due to the lack of water permeability of the ground, rainwater cannot penetrate into the ground, causing the lack of exchange of urban heat and moisture, leading to the difficulty in normal regulation of urban temperature and humidity, and resulting in the urban "heat island phenomenon". At the same time, since rainwater cannot penetrate into the ground in a short time, a large amount of rainwater can only be discharged into rivers through underground drainage facilities, which not only increases the burden of drainage facilities, but also easily causes urban waterlogging in heavy rain, causing serious safety hazards to urban management.

[0003] The prior art with publication number CN108439879A discloses a water-permeable pavement paving material and a preparation method thereof. Fly ash is used to fill into the large pores of ceramic coarse aggregate together with vermiculite, diatomite and zeolite small particles to change the distribution of the pores, forming gravel layers with different particle sizes. At the same time, fly ash itself is used to replace cement paste as a cementing material together with a polymer emulsion, so that the porosity of the water-permeable concrete is greatly improved, the water permeability of the water-permeable concrete is improved, the effective porosity is ensured, and the water-permeable concrete has a high continuous porosity and a high permeability coefficient, thereby achieving a high drainage function. The water permeability of the method still needs to be improved, and the treatment of the original pavement building material also has problems.

[0004] Therefore, it is of great significance to develop a low-carbon type full water-permeable paving material which can utilize the original pavement building material, has high overall strength, good water and air permeability, is ecological, energy-saving, low-carbon and environmentally friendly, can meet the pavement performance, is coordinated with the natural environment, can improve the heat balance of the ground, enhance the circulation of water on the ground, increase the underground water resources of the city, relieve the heat island effect and improve the climate. SUMMARY

[0005] 1. Technical problems to be solved: In view of the above technical problems, the present application provides a low-carbon type water-permeable paving material and a preparation method thereof.

[0006] 2. Technical solutions: A low-carbon type permeable pavement material, the results include soil layer, sand and gravel grading layer, pervious concrete base layer, pervious concrete surface layer and surface paint protective layer; the upper surface of the soil layer is paved with the sand and gravel grading layer, the upper surface of the sand and gravel grading layer is paved with the pervious concrete base layer, the upper surface of the pervious concrete base layer is paved with the pervious concrete surface layer, and the upper surface of the pervious concrete surface layer is sprayed with the surface paint protective layer; characterized in that: the upper surface of the pervious concrete base layer and the lower surface of the pervious concrete surface layer are corrugated, and the corrugated peaks and valleys of the two are embedded with each other; the shape of the corrugated is UV shape, the corrugated angle is radian angle, and the size of the corrugated angle is 90°~150°.

[0007] Further, the pervious concrete base layer is prepared from 70~80 parts of recycled aggregate, 3~5 parts of deionized water, 10~12 parts of composite mineral powder, and 12~15 parts of polymer emulsion.

[0008] Further, the recycled aggregate is the crushed and screened granules with particle sizes of 3~7mm and 7~10mm obtained by washing the original pavement building materials, and the granules with the two particle sizes are mixed after being washed and dried again.

[0009] Further, the mass ratio of the granules with particle sizes of 3~7mm to 7~10mm is 1:1~1:2.

[0010] Further, the composite mineral powder is prepared by crushing, sieving, drying, ball milling fly ash to a specific surface area of 300~400m 2 / kg, and then ball milling the fly ash with vermiculite, recycled powder, diatomite, bentonite and zeolite to a specific surface area of 400~500m 2 / kg.

[0011] Further, the weight parts of the fly ash, vermiculite, diatomite, bentonite and zeolite are 10~15 parts of fly ash, 5~10 parts of recycled powder, 1~1.5 parts of vermiculite, 1~2 parts of diatomite, 1~2 parts of bentonite and 1~2 parts of zeolite.

[0012] Further, the polymer emulsion is one or more of polyacrylate emulsion, ethylene-vinyl acetate copolymer emulsion, polyvinyl acetate emulsion, styrene-acrylic emulsion, polyvinyl propionate emulsion and chloroethylene-vinylidene chloride copolymer emulsion.

[0013] A preparation method of a low-carbon type permeable pavement material, comprising the following steps: Step one: crush the fly ash through a 100 mesh sieve, dry it, ball mill the dried fly ash to a specific surface area of 300~400m 2 / kg, then add recycled powder, vermiculite, diatomite, bentonite and zeolite and continue to ball mill to a specific surface area of 400~500m2 / kg, to obtain the composite mineral powder; Step two: crush and screen the original pavement construction material to obtain the 3-7mm and 7-10mm granules, mix the two kinds of granules after water washing and drying, to obtain the recycled aggregate; Step three: take 7~10mm recycled aggregate and 1 / 6 deionized water, put them into the mixing barrel and mix for 1~2min, then add 1 / 6 composite mineral powder, stir for 1~2min at 150~200r / min, then add 1 / 6 deionized water and 1 / 6 composite mineral powder, continue to stir for 1~2min, then add 1 / 6 deionized water, 1 / 6 composite mineral powder and polymer emulsion, continue to stir for 3~5min, to obtain the pervious concrete base paving material; Step four: take 3~7mm recycled aggregate and 1 / 6 deionized water, put them into the mixing barrel and mix for 1~2min, then add 1 / 6 composite mineral powder, stir for 1~2min at 150~200r / min, then add 1 / 6 deionized water and 1 / 6 composite mineral powder, continue to stir for 1~2min, then add 1 / 6 deionized water, 1 / 6 composite mineral powder and polymer emulsion, continue to stir for 3~5min, to obtain the pervious concrete surface paving material; Step five: spread the pervious concrete base paving material on the sand and pebble graded layer, use the corrugated road roller to compact, and form the corrugated structure pervious concrete base after curing for 4~6h; the road roller of the corrugated road roller is corrugated road roller, and the surface of the corrugated road roller is provided with UV-shaped corrugated concave-convex lines; the corrugated angle of the concave-convex lines extends in the same direction as the movement direction of the road roller; Step six: spread the pervious concrete surface paving material on the corrugated structure pervious concrete base, use the road roller to compact, and form the low-carbon pervious pavement after curing for 4~6h.

[0014] 3. Beneficial effects: The low-carbon type water-permeable pavement material provided by the method creatively adopts a corrugated pavement structure; the water-permeable path is changed, the water-permeable area and the water-permeable mode are increased, the blockage is prevented, and the water-permeable efficiency is improved. Meanwhile, the corrugated pavement structure optimizes the mechanical properties of the water-permeable pavement and improves the bearing capacity, and the strength is significantly increased. (1) The corrugated pavement structure is creatively adopted in the design; the water-permeable pavement forms a mechanical support system similar to an arch bridge, can effectively disperse the load pressure and convert it into transverse stress, and reduces the local compression strength requirement. (2) The bearing capacity of the water-permeable pavement is enhanced; the UV-shaped D corrugated structure of the water-permeable pavement can effectively increase the strength and toughness, can effectively bear the horizontal load and the vertical load, and fully plays the overall bearing capacity of the water-permeable pavement. (3) The overall performance of the water-permeable pavement is improved; the corrugation of the water-permeable pavement has a certain anti-seismic property, and can improve the overall performance of the water-permeable pavement. (4) The wave effect of the water-permeable pavement is improved; the corrugated wave structure can more effectively distribute the load when subjected to vertical pressure. Each wave crest and wave trough plays a supporting role, reducing the single-point stress condition, thereby enhancing the overall compression resistance of the water-permeable pavement. (5) The shear resistance of the water-permeable pavement is improved; the corrugated wave shape effectively resists the horizontal shear force, so that the water-permeable pavement structure is more stable when bearing the lateral load. (6) The material utilization rate of the water-permeable pavement is improved; the corrugated structure design fully utilizes the mechanical properties of the material, especially in terms of lightweight and high strength. Through reasonable size design and material selection, the material consumption can be minimized while ensuring the strength. (7) The cross section of the water-permeable pavement is optimized; the cross section shape of the corrugation is carefully designed to achieve lightweight under the premise of ensuring sufficient rigidity. (8) The energy absorption and buffering capacity of the water-permeable pavement is improved; another notable feature of the corrugated structure is its excellent energy absorption capacity. When subjected to impact or vibration, the corrugated wave structure will undergo elastic deformation, absorbing and dispersing a large amount of energy. (9) The dynamic response of the water-permeable pavement is improved; under dynamic loading conditions, the corrugated structure can slow down the impact force through its unique deformation mode, prolong the impact time, and thus reduce the peak stress. (10) The recovery of the water-permeable pavement is improved; the corrugated structure has good recovery, i.e., it can return to its original shape after unloading, which makes it suitable for use in situations that require repeated use. (11) The environmental adaptability of the water-permeable pavement is improved; the corrugated structure is also favored due to its ease of construction, low cost, and other advantages. These characteristics enable it to maintain good mechanical properties and service life under various environmental conditions. BRIEF DESCRIPTION OF DRAWINGS

[0015] Figure 1 A cross-sectional view of a road paved with the water-permeable pavement material of the present application; Figure 2 A structural view of the water-permeable concrete base layer and the water-permeable concrete surface layer of the present application; Figure 3This is a structural diagram of the roller of the corrugated roller in this invention; Figure 4 This is a schematic diagram of the corrugated road roller in this invention; Figure 5 This is a schematic diagram of the road roller in this invention.

[0016] Attached diagram labels: 1. Plain soil layer; 2. Gravel and sand graded layer; 3. Permeable concrete base layer; 4. Permeable concrete surface layer; 5. Topcoat protective layer; 6. Corrugated roller. Detailed Implementation

[0017] The present invention will now be described in detail with reference to the accompanying drawings.

[0018] As attached Figure 1 , 2 As shown, a low-carbon permeable pavement material comprises a subgrade soil layer 1, a gravel-pebble graded layer 2, a permeable concrete base layer 3, a permeable concrete surface layer 4, and a protective topcoat layer 5. The subgrade soil layer is covered with a gravel-pebble graded layer on its upper surface, the gravel-pebble graded layer is covered with a permeable concrete base layer on its upper surface, the permeable concrete base layer is covered with a permeable concrete surface layer on its upper surface, and the permeable concrete surface layer is coated with a protective topcoat layer. The material is characterized in that the upper surface of the permeable concrete base layer and the lower surface of the permeable concrete surface layer are both corrugated, with the corrugations interlocking. The corrugated shape is UV-shaped, with the angles being arc angles ranging from 90° to 150°.

[0019] Furthermore, the permeable concrete base layer is prepared from 70-80 parts of recycled aggregate, 3-5 parts of deionized water, 10-12 parts of composite mineral powder, and 12-15 parts of polymer emulsion.

[0020] Furthermore, the recycled aggregate is prepared by washing, crushing and screening the original road construction materials to obtain fragments with particle sizes of 3~7mm and 7~10mm, and then mixing the fragments of the two particle sizes after washing and drying them again.

[0021] Furthermore, the mass ratio of the fragments with a particle size of 3~7mm to 7~10mm is 1:1~1:2.

[0022] Furthermore, the composite mineral powder is prepared by pulverizing and sieving fly ash, drying and ball milling it to a specific surface area of ​​300-400 m2 / kg, and then mixing it with vermiculite, recycled powder, diatomaceous earth, bentonite and zeolite and ball milling it to a specific surface area of ​​400-500 m2 / kg; the recycled powder is fine powder obtained by washing, pulverizing and screening the original road construction materials.

[0023] Further, the weight parts of the fly ash, vermiculite, diatomite, bentonite, and zeolite are 10-15 parts of fly ash, 5-10 parts of regenerated powder, 1-1.5 parts of vermiculite, 1-2 parts of diatomite, 1-2 parts of bentonite, and 1-2 parts of zeolite.

[0024] Further, the polymer emulsion is one or more of polyacrylate emulsion, ethylene-vinyl acetate copolymer emulsion, polyvinyl acetate emulsion, styrene-acrylic emulsion, polyvinyl propionate emulsion, and chloroethylene-vinylidene chloride copolymer emulsion.

[0025] A preparation method of a low-carbon type water-permeable paving material, comprising the following steps: Step one: after the fly ash is crushed through a 100-mesh sieve and dried, the dried fly ash is ball milled to a specific surface area of 300-400 m2 / kg, and then the regenerated powder, vermiculite, diatomite, bentonite, and zeolite are added and ball milled to a specific surface area of 400-500 m2 / kg to obtain a composite mineral powder.

[0026] Step two: the original pavement building materials are crushed and sieved to obtain crushed particles with a particle size of 3-7 mm and 7-10 mm, and the crushed particles with the two particle sizes are mixed after being washed and dried to obtain regenerated aggregates.

[0027] Step three: 7-10 mm regenerated aggregates and 1 / 6 deionized water are put into a mixing barrel and stirred and mixed for 1-2 min, 1 / 6 composite mineral powder is then added, and stirring is performed at 150-200 r / min for 1-2 min, 1 / 6 deionized water and 1 / 6 composite mineral powder are then added, and stirring is continued for 1-2 min, 1 / 6 deionized water, 1 / 6 composite mineral powder, and polymer emulsion are then added, and stirring is continued for 3-5 min to obtain a water-permeable concrete base paving material.

[0028] Step four: 3-7 mm regenerated aggregates and 1 / 6 deionized water are put into a mixing barrel and stirred and mixed for 1-2 min, 1 / 6 composite mineral powder is then added, and stirring is performed at 150-200 r / min for 1-2 min, 1 / 6 deionized water and 1 / 6 composite mineral powder are then added, and stirring is continued for 1-2 min, 1 / 6 deionized water, 1 / 6 composite mineral powder, and polymer emulsion are then added, and stirring is continued for 3-5 min to obtain a water-permeable concrete surface layer paving material.

[0029] Step five: the water-permeable concrete base paving material is spread on a sand and pebble graded layer, and a corrugated road roller is used for compaction, and a corrugated structure water-permeable concrete base is formed after curing for 4-6 h; the compaction roller of the corrugated road roller is a corrugated road roller, and the surface of the corrugated road roller is provided with UV-shaped corrugated concave-convex patterns; the corrugated angle of the concave-convex patterns extends in the same direction as the movement direction of the compaction roller.

[0030] The compaction roller of the corrugated road roller and the corrugated road roller are as shown in the accompanying drawings Figure 3 ,4 as shown. Figure 5 is a schematic view of a road roller.

[0031] Step six: spread the water permeable concrete surface layer paving material on the corrugated structure water permeable concrete base layer, use the road roller to compact, and form the low-carbon water permeable pavement after curing for 4-6 hours.

[0032] The following examples are implemented by the following steps: Step one: after the fly ash is crushed through a 100-mesh sieve and dried, the dried fly ash is ball milled to a specific surface area of 300-400 m2 / kg, and then the regenerated powder, 10 vermiculite, diatomite, bentonite, and zeolite are added for further ball milling to a specific surface area of 400-500 m2 / kg, to obtain a composite mineral powder.

[0033] Step two: crush and screen the original pavement construction materials to obtain crushed particles with particle sizes of 3-7 mm and 7-10 mm, mix the crushed particles of the two particle sizes after water washing and drying, to obtain recycled aggregates.

[0034] Step three: take 7-10 mm recycled aggregates and 1 / 6 deionized water, load them into a mixing barrel, and stir and mix for 1-2 min, then add 1 / 6 composite mineral powder, stir at 150-200 r / min for 1-2 min, then add 1 / 6 deionized water and 1 / 6 composite mineral powder, continue to stir for 1-2 min, then add 1 / 6 deionized water, 1 / 6 composite mineral powder, and polymer emulsion, and continue to stir for 3-5 min, to obtain a water permeable concrete base layer paving material.

[0035] Step four: take 3-7 mm recycled aggregates and 1 / 6 deionized water, load them into a mixing barrel, and stir and mix for 1-2 min, then add 1 / 6 composite mineral powder, stir at 150-200 r / min for 1-2 min, then add 1 / 6 deionized water and 1 / 6 composite mineral powder, continue to stir for 1-2 min, then add 1 / 6 deionized water, 1 / 6 composite mineral powder, and polymer emulsion, and continue to stir for 3-5 min, to obtain a water permeable concrete surface layer paving material.

[0036] Step five: spread the water permeable concrete base layer paving material on the sand and pebble graded layer, use the corrugated road roller to compact, and form a corrugated structure water permeable concrete base layer after curing for 4-6 hours; the road roller roller of the corrugated road roller is a corrugated road roller, and the surface of the corrugated road roller is provided with UV-shaped corrugated concave-convex patterns; the corrugated angle of the concave-convex patterns extends in the same direction as the movement direction of the road roller.

[0037] Step six: spread the water permeable concrete surface layer paving material on the corrugated structure water permeable concrete base layer, use the road roller to compact, and form the low-carbon water permeable pavement after curing for 4-6 hours.

[0038] Example 1: The mass ratio of the composite mineral powder is: 10 parts of fly ash, 5 parts of recycled powder, 1 part of vermiculite, 2 parts of diatomite, 2 parts of bentonite, and 2 parts of zeolite; The mass ratio of the recycled aggregate is 1:1 for 3-7 mm and 7-10 mm crushed particles.

[0039] The mass ratio of the recycled aggregate, the composite mineral powder, the polymer emulsion preparation, and the deionized water is 70:10:12:4.

[0040] The size of the ridge angle is 90°.

[0041] The water permeability coefficient of the obtained water permeable pavement material is 3.0 mm / s, and the compressive strength reaches 42.5 MPa.

[0042] Example 2: The mass ratio of the composite mineral powder is: 12 parts of fly ash, 10 parts of recycled powder, 1.2 parts of vermiculite, 1.5 parts of diatomite, 1.5 parts of bentonite, and 1 part of zeolite; The mass ratio of the recycled aggregate is 1:1 for 3-7 mm and 7-10 mm crushed particles.

[0043] The mass ratio of the recycled aggregate, the composite mineral powder, the polymer emulsion preparation, and the deionized water is 75:10:13:5.

[0044] The size of the ridge angle is 120° The water permeability coefficient of the obtained water permeable pavement material is 2.5 mm / s, and the compressive strength reaches 30.0 MPa.

[0045] Example 3: The mass ratio of the composite mineral powder is: 15 parts of fly ash, 8 parts of recycled powder, 1.5 parts of vermiculite, 1 part of diatomite, 1 part of bentonite, and 2 parts of zeolite; The mass ratio of the recycled aggregate is 1:2 for 3-7 mm and 7-10 mm crushed particles.

[0046] The mass ratio of the recycled aggregate, the composite mineral powder, the polymer emulsion preparation, and the deionized water is 80:10:15:5. The water permeability coefficient of the obtained water permeable pavement material is 2.7 mm / s, and the compressive strength reaches 37.5 MPa.

[0047] Example 4: The mass ratio of the composite mineral powder is: 13 parts of fly ash, 10 parts of recycled powder, 2 parts of vermiculite, 1 part of diatomite, 1 part of bentonite, and 1 part of zeolite; The proportioning of the recycled aggregate is that the mass ratio of 3-7mm and 7-10mm broken particles is 1:2.

[0048] The proportioning of the recycled aggregate, composite mineral powder, polymer emulsion and deionized water is 75:12:15:3.

[0049] The size of the ridge angle is 150°.

[0050] The water permeability and the compressive strength of the water permeable pavement material are measured, the water permeability coefficient of the obtained water permeable pavement material is 2.8mm / s, and the compressive strength reaches 42.5MPa.

[0051] Although the present application has been disclosed in the preferred embodiments as above, they are not intended to limit the present application, and any person skilled in the art can make various changes or modifications without departing from the spirit and scope of the present application, therefore the protection scope of the present application should be defined by the protection scope of the claims of the present application.

Claims

1. A low-carbon permeable pavement material, comprising a subgrade layer, a gravel-pebble graded layer, a permeable concrete base layer, a permeable concrete surface layer, and a protective topcoat layer; wherein the gravel-pebble graded layer is laid on the upper surface of the subgrade layer, the permeable concrete base layer is laid on the upper surface of the gravel-pebble graded layer, the permeable concrete surface layer is laid on the upper surface of the permeable concrete base layer, and the protective topcoat layer is sprayed onto the upper surface of the permeable concrete surface layer; characterized in that: The upper surface of the permeable concrete base layer and the lower surface of the permeable concrete surface layer are both corrugated, with the corrugations interlocking and interlocking. The corrugation is UV-shaped, with the corners being arc angles, and the angles being 90° to 150°.

2. The low-carbon permeable paving material according to claim 1, characterized in that: The permeable concrete base layer is prepared from 70-80 parts recycled aggregate, 3-5 parts deionized water, 10-12 parts composite mineral powder, and 12-15 parts polymer emulsion.

3. The low-carbon permeable paving material according to claim 2, characterized in that: The recycled aggregate is prepared by washing, crushing and screening the original road construction materials to obtain fragments with particle sizes of 3~7mm and 7~10mm. The fragments of the two particle sizes are then washed and dried again and mixed together.

4. The low-carbon permeable paving material according to claim 3, characterized in that: The mass ratio of the fragments with a particle size of 3~7mm to 7~10mm is 1:1~1:

2.

5. The low-carbon permeable pavement material according to claim 1, characterized in that: The composite mineral powder is made by crushing, sieving, drying, and ball milling fly ash to a specific surface area of ​​300-400 m². 2 / kg, then mixed with vermiculite, recycled powder, diatomaceous earth, bentonite, and zeolite and ball-milled until the specific surface area is 400-500m². 2 / kg is obtained; the recycled powder is fine powder obtained by washing, crushing and screening the original road construction materials.

6. The low-carbon permeable pavement material according to claim 5, characterized in that: The fly ash, vermiculite, diatomite, bentonite, and zeolite are present in the following weight proportions: 10-15 parts fly ash, 5-10 parts recycled powder, 1-1.5 parts vermiculite, 1-2 parts diatomite, 1-2 parts bentonite, and 1-2 parts zeolite.

7. The low-carbon permeable pavement material according to claim 1, characterized in that: The polymer emulsion is one or more of the following: polyacrylate emulsion, ethylene-vinyl acetate copolymer emulsion, polyvinyl acetate emulsion, styrene-acrylic emulsion, polyvinyl propionate emulsion, and vinyl chloride-vinylidene chloride copolymer emulsion.

8. A method for preparing a low-carbon permeable pavement material, used to prepare the permeable pavement material as described in claims 1-7, characterized in that: Includes the following steps: Step 1: Crush the fly ash through a 100-mesh sieve and dry it. Then, ball mill the dried fly ash until the specific surface area is 300-400 m². 2 / kg, then add recycled powder, vermiculite, diatomaceous earth, bentonite, and zeolite, and continue ball milling until the specific surface area is 400~500m². 2 / kg, yielding compound mineral powder; Step 2: Crush and screen the original road construction materials to obtain fragments with a particle size of 3-7mm and 7-10mm. After washing and drying the fragments of the two particle sizes, mix them to obtain recycled aggregate. Step 3: Take 7-10mm recycled aggregate and 1 / 6 deionized water, put them into a mixing bucket and stir for 1-2 minutes. Then add 1 / 6 composite mineral powder and stir at 150-200 r / min for 1-2 minutes. Then add 1 / 6 deionized water and 1 / 6 composite mineral powder and continue stirring for 1-2 minutes. Then add 1 / 6 deionized water, 1 / 6 composite mineral powder and polymer emulsion and continue stirring for 3-5 minutes to obtain permeable concrete base paving material. Step 4: Take 3-7mm recycled aggregate and 1 / 6 deionized water, put them into a mixing bucket and stir for 1-2 minutes. Then add 1 / 6 composite mineral powder and stir at 150-200 r / min for 1-2 minutes. Then add 1 / 6 deionized water and 1 / 6 composite mineral powder and continue stirring for 1-2 minutes. Then add 1 / 6 deionized water, 1 / 6 composite mineral powder and polymer emulsion and continue stirring for 3-5 minutes to obtain permeable concrete pavement material. Step 5: Spread the permeable concrete base course material on the gravel-aggregate layer, compact it with a corrugated roller, and cure it for 4-6 hours to form a corrugated permeable concrete base course; the roller of the corrugated roller is a corrugated roller, and the surface of the corrugated roller is provided with UV-shaped corrugated textures; the extension direction of the corners of the textures is the same as the movement direction of the roller; Step 6: Spread the permeable concrete pavement material on the corrugated permeable concrete base layer, compact it with a road roller, and form a low-carbon permeable pavement after curing for 4-6 hours.

Citation Information

Patent Citations

  • Permeable pavement paving material and preparation method thereof

    CN108439879A